Effects of Emotionally Focused Couple Therapy on Reducing Depression and Marital Conflicts in Employed Couples - Alireza Momeni; Khosro Ramezani; Alireza Maredpour (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Employment of couples have a considerable effect on their marital life and may cause the couple not to respond to each other's needs in a timely manner. In these circumstances, depression and marital conflict is very likely. Objectives: The present study aimed to investigate the effectiveness of emotionally focused couple therapy (EFCT) on reducing depression and marital conflicts in employed couples in Ramhormoz-Iran. Methods: A randomized clinical trial study based on a pretest-posttest control group design was conducted. The study population consisted of all couples employed in government organizations of Ramhormoz-Iran. Based on the inclusion criteria, 50 couples (100 people) were selected as the sample and randomly assigned to the experimental and control groups. The experimental group underwent ten 90-minute sessions per week of emotionally focused couple therapy. The research instruments included the Beck's Depression Inventory and Marital Conflict Questionnaire. Data were analyzed by multivariate analysis of covariance. Results: The results indicated that there was a significant difference between the experimental and control groups in the score of depression and marital conflicts. The mean (SD) of the post- intervention scores for depression and marital conflicts in the experimental group were 27.32 (4.17) and 116.72 (9.34) respectively. EFCT significantly reduced the mean score of depression and marital conflicts in the experimental group compared with the control group (p<0.001). Conclusion: EFCT was effective in reducing depression and marital conflicts among employed couples. Therefore, EFCT workshops can effectively help employed couples mitigate emotional problems.